A Comparative Analysis of the Evolution of Pidgin and Creole Languages Globally - Fitriani, Namiyah; Adjiji, Fatma Dewi; Susanto, Djoko (Universitas Pamulang, 2025)
Pidgins and creoles are two unique language forms, born out of linguistic contact in various global contexts, including trade, colonialism and migration. Pidgins evolved as simple means of communication between speakers of different languages, while creoles emerged when pidgins became the mother tongue of certain communities, expanding their grammatical complexity and vocabulary. The aim of the research is to analyze the evolution of pidgin and creole languages globally, including the problems, procedures, relationships of activities, attitudes, views, and influences of certain phenomena. The research compares the evolution of pidgins and creoles globally, exploring the processes of pidginization, creolization, and their distribution and characteristics in different regions. It highlights the social and linguistic dynamics underlying the formation of these languages, while demonstrating the significant role of pidgins and creoles in understanding the evolution of human language. This research uses a qualitative approach with descriptive methods to accurately describe facts and situations in society. The research methods include a literature study, where researchers collect data from secondary sources such as books and journals, as well as a historical approach that reviews the development of pidgins and creoles in the context of trade, colonialism and migration. This approach allowed for an in-depth exploration of relevant linguistic and socio-cultural data. The results of this analysis provide deep insights into the relationship between language, culture and history in a changing global context.